Mg/W-codoped vanadium dioxide thin films with enhanced visible transmittance and low phase transition temperature - Long, Yi (2015)
Vanadium dioxide (VO2), with a reversible phase transition near ambient temperature, has been found to be a promising candidate for energy-saving smart windows. However, its use is constrained by its low visible transmission (Tlum) and high transition temperature (τc). In this paper, by codoping tungsten (W) and magnesium (Mg) in VO2, a good combination of low τc (~35 °C) and high Tlum (81.3%) was achieved. The τc declines with decreasing Mg doping level in Mg/W-codoped samples, which is the opposite effect of doping with only Mg, suggesting a synergistic effect of the two dopants arising from the e− and h+ carrier neutralization. In addition, the band gap of Mg/W-codoped VO2 was gradually widened; this is attributed to the depressed absorption, which enhanced the Tlum.